2016
DOI: 10.1016/j.fertnstert.2016.07.1075
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in the pelvic cavity and its role in the pathogenesis of endometriosis

Abstract: Endometriosis is a disorder associated with a general inflammatory response in the peritoneal cavity. Oxidative stress is a potential factor involved in the pathophysiology of this disease, and reactive oxygen species (ROS) are implicated in this process. Indeed, in healthy individuals, ROS and antioxidants are in balance, but when balance is tipped toward an overabundance of ROS, oxidative stress occurs and can impact the entire reproductive lifespan of a woman. Reactive oxygen species are intermediaries prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
174
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 180 publications
(181 citation statements)
references
References 64 publications
(125 reference statements)
2
174
1
4
Order By: Relevance
“…As ectopic endometrium experiences cyclic bleeding, cell‐free hemoglobin and its highly toxic by‐products heme and iron are released from erythrocytes in and around lesions. Lysis of erythrocytes by macrophages results in iron overload, inducing iron‐mediated damage, oxidative injury and inflammation and oxidative stress . Consistently, granulosa cells from patients with infertility and endometriosis exhibit more signs of severe oxidative DNA damage when compared with cells from other patients with infertility .…”
Section: Changing Pressure For Genomic Alteration Due To Oxidative Stmentioning
confidence: 84%
See 3 more Smart Citations
“…As ectopic endometrium experiences cyclic bleeding, cell‐free hemoglobin and its highly toxic by‐products heme and iron are released from erythrocytes in and around lesions. Lysis of erythrocytes by macrophages results in iron overload, inducing iron‐mediated damage, oxidative injury and inflammation and oxidative stress . Consistently, granulosa cells from patients with infertility and endometriosis exhibit more signs of severe oxidative DNA damage when compared with cells from other patients with infertility .…”
Section: Changing Pressure For Genomic Alteration Due To Oxidative Stmentioning
confidence: 84%
“…Lysis of erythrocytes by macrophages results in iron overload, inducing iron-mediated damage, oxidative injury and inflammation and oxidative stress. 375 Consistently, granulosa cells from patients with infertility and endometriosis exhibit more signs of severe oxidative DNA damage when compared with cells from other patients with infertility. 377 Expression levels of 8-hydroxydeoxyguanosine (8-Oh-dG), a sensitive indicator of DNA damage resulting from oxidative stress, are reported to be significantly higher in samples of normal ovarian cortex surrounding endometriotic cysts.…”
Section: Guomentioning
confidence: 85%
See 2 more Smart Citations
“…Indeed, Kitajima et al (4) clearly demonstrated the ''burn-out'' effect on the ovarian reserve induced by the ''toxic'' intraovarian environment and inflammation due to the presence of ovarian endometriomas, leading to increased fibrosis, loss of cortex-specific stroma, vascularization defects, and ultimately, impaired follicular maturation and greater follicular atresia. Moreover, the role of oxidative stress should not be overlooked (5), because excessive release of reactive oxygen species alters cellular function by dysregulating protein activity and gene expression, resulting in harmful effects (5).…”
mentioning
confidence: 99%